2017
DOI: 10.1002/ejoc.201601377
|View full text |Cite
|
Sign up to set email alerts
|

Flavin‐Mediated Visible‐Light [2+2] Photocycloaddition of Nitrogen‐ and Sulfur‐Containing Dienes

Abstract: Abstract:The [2+2] photocycloaddition mediated by 1-butyl-3-methyl-7,8-dimethoxyalloxazine (1) has been found to be an effective tool for cyclising ω-phenyl-and ω,ω′-diphenyl-4-aza-1,6-heptadienes, in which the nitrogen atom is protected by acylation or quaternisation, towards the synthesis of a variety of phenyl-and diphenyl-3-azabicyclo[3.2.0]heptanes and their corresponding quaternary salts. Thia derivatives, with the sulfur atom in the form of a sulfone group, underwent an analogous cyclisation. Advantageo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Analogously, isomeric ( E , E )‐ 12 a and ( Z , Z )‐ 12 a afforded an almost identical mixture of stereoisomers of cyclobutane 16 a . After irradiation of 1‐phenylpropene, 1‐( p ‐methoxyphenyl)propene and 1‐(4‐methoxyphenyl)but‐2‐en‐1‐one in the presence of alloxazine 2 e , E / Z isomerization occurred, and it was also observed in the case of several substituted aromatic alkenes producing a mixture enriched with the Z‐isomer . The [2+2] cyclisation was not observed in the case of these simple alkenes, which can be explained by the very short lifetime of the styrene triplet excited state disfavouring the intermolecular process…”
Section: Resultsmentioning
confidence: 99%
“…Analogously, isomeric ( E , E )‐ 12 a and ( Z , Z )‐ 12 a afforded an almost identical mixture of stereoisomers of cyclobutane 16 a . After irradiation of 1‐phenylpropene, 1‐( p ‐methoxyphenyl)propene and 1‐(4‐methoxyphenyl)but‐2‐en‐1‐one in the presence of alloxazine 2 e , E / Z isomerization occurred, and it was also observed in the case of several substituted aromatic alkenes producing a mixture enriched with the Z‐isomer . The [2+2] cyclisation was not observed in the case of these simple alkenes, which can be explained by the very short lifetime of the styrene triplet excited state disfavouring the intermolecular process…”
Section: Resultsmentioning
confidence: 99%
“…Each of these methods usually require the use of transition‐metal catalysis or UV irradiation, except for the case of intramolecular cycloaddition of keteniminium salts,, thus typically being limited in substrate scope. To synthesize 1‐substituted 3‐azabicyclo[3.2.0]heptane derivatives, the flavin‐mediated and copper(I)‐catalyzed [2+2] photocycloadditions were applied, providing 1‐phenyl and 1‐methyl‐substituted analogues, respectively. To date, all the aforementioned methods were not adopted for the preparation of bifunctional 1‐substituted 3‐azabicyclo[3.2.0]heptanes, although its isomer – 2‐azabicyclo[3.2.0]heptane‐1‐carboxylic acid has been obtained using a similar transformation, followed by oxidation of the furan ring with NaIO 4 /RuCl 3 .…”
Section: Introductionmentioning
confidence: 99%
“…To synthesize 1-substituted 3-azabicyclo[3. 2.0]heptane derivatives, the flavin-mediated [12] and copper(I)-catalyzed [13] [2+2] photocycloadditions were applied, providing 1-phenyl and 1-methyl-substituted analogues, respectively. To date, all the aforementioned methods were not adopted for the preparation of bifunctional 1-substituted 3-azabicyclo[3.…”
Section: Introductionmentioning
confidence: 99%
“…[11] The iridium-based catalyst, Ir[(dtbbpy)(dF(CF 3 )ppy) 2 ]PF 6 was a suitable triplet sensitizer for this [2 + 2] photocycloaddition via visible light. [14] Already in 1976, Oppolzer et al [15] have observed in the thermolysis of N-benzylsubstituted cinnamyl cinnamide the corresponding aza-bicyclo-[3.2.0]-heptanone as byproduct, whose generation was confirmed afterwards by an UVmediated [2 + 2] photocycloaddition. [12] The intramolecular variant afforded mostly carbocycles or oxygen-containing heterocycles 2 (Scheme 1).…”
mentioning
confidence: 99%
“…If the aromatic substituent is placed on the amine moiety (5 c-tBu, 5 c-Bn) the [2 + 2] reaction is complete within 3-4 h (entries 5, 6), whereas in the case of 5 d-tBu or 5 c-Bn the [2 + 2] photocycloaddition takes approximately five times longer to reach full conversion (entries 8,9). Additionally, if the aromatic substituent is located on the carbonyl side (R 2 ) a better diastereoselectivity is achieved (entries 8-10, [12][13][14]. Additionally, if the aromatic substituent is located on the carbonyl side (R 2 ) a better diastereoselectivity is achieved (entries 8-10, [12][13][14].…”
mentioning
confidence: 99%